Behaviour of corrugated web girders subjected to lateral-torsional buckling: Experimental tests and numerical modelling. (October 2021) - Elkawas, A.A.; Hassanein, M.F.; El Hadidy, A.M.; El-Boghdadi, M.H.; Elchalakani, Mohamed
Abstract: Corrugated plates are gaining increasing attention from researchers based on their recent extensive use in structural engineering, thanks to their potential to provide lighter and more economic structures. However, tests on the flexural behaviour of trapezoidally corrugated web girders (CWGs) are still scarce in the literature. Accordingly, the purpose of this paper is to provide the fundamental behaviour of laterally-unrestrained trapezoidally CWGs by experimental and numerical investigations. The middle parts of the specimens are loaded by pure bending moment by adopting the four-point loading process. Firstly, three CWGs are tested experimentally by changing the flange width and web height, with corrugation dimensions kept the same. The flange width varies from 80 mm to 100 mm and the web height changes from 300 mm to 400 mm. The girders are found to fail by the lateral-torsional buckling mechanism without any local flange buckling or web distortion. After that, ABAQUS software is used to increase the data required to explore the influence of different parameters on the behaviour of CWGs. The accuracy of the finite element (FE) models is verified by using the test results. This is followed by parametric studies investigating the behaviour of CWGs through the variations of the flange width, flange thickness and web height. The results indicate that increasing flange width is an effective solution for increasing the ultimate moment capacity of CWGs which is accompanied by a slight increase in the lateral displacement of the girder. Furthermore, girders with large flange widths have high load carrying capacities compared with the material used. Additionally, the results show that increasing the web height has a positive effect on the moment capacities of CWGs.